The cost of transporting cereals in West Africa - Mercier, Stephanie (International Food Policy Research Institute, 2018)
This study examines transportation alternatives for moving cereals into position for storage under the West African Food Security Regional Reserve agreed to by the Economic Community of West African States (ECOWAS) in 2013, for which cereals were first procured in 2017. It describes the reserve’s management structure and rules for procuring commodities, both types of cereals and preferred sourcing for those purchases. The study identified countries within the 15-nation ECOWAS region where the desired types of cereals are available, and recent sources for imported rice, which is a preferred staple food in ECOWAS member countries even though the region is far from self-sufficient in this commodity. Despite the poor quality of roads and commercial trucks in much of West Africa and the official and unofficial barriers to movement of products across national borders, surface transportation of cereal shipments is determined to be the most economical mode of transportation for servicing the stockholding facilities of the regional reserve for goods originating within the continent. Significant investments are scheduled to be made in railroads that cross national borders within West Africa, as well as in infrastructure for river transport, including inland port facilities and improving navigable channels in key regional river systems, but those modes are not yet viable alternatives to road transport for most of the West Africa region.